Trends in user-initiated health information exchange in the inpatient, outpatient, and emergency settings. (17th October 2020) - Rahurkar, Saurabh; Vest, Joshua R; Finnell, John T; Dixon, Brian E
Abstract: Prior research on health information exchange (HIE) typically measured provider usage through surveys or they summarized the availability of HIE services in a healthcare organization. Few studies utilized user log files. Using HIE access log files, we measured HIE use in real-world clinical settings over a 7-year period (2011-2017). Use of HIE increased in inpatient, outpatient, and emergency department (ED) settings. Further, while extant literature has generally viewed the ED as the most relevant setting for HIE, the greatest change in HIE use was observed in the inpatient setting, followed by the ED setting and then the outpatient setting. Our findings suggest that in addition to federal incentives, the implementation of features that address barriers to access (eg, Single Sign On), as well as value-added services (eg, interoperability with external data sources), may be related to the growth in user-initiated HIE.